Closed Genome Sequence of Vibrio cholerae O1 El Tor Inaba Strain A1552 - Allué-Guardia, Anna (Genome Announc, 2018)
Vibrio cholerae is a Gram-negative waterborne human pathogen and the causative agent of cholera. Here, we present the complete genome sequence of the seventh pandemic O1 biovar El Tor Inaba strain A1552 isolated in 1992. This clinical strain has served as an important model strain for studying cholera pathogenicity traits.